Comprehensive toxicity risk profiling in radiation therapy for head and neck cancer: A new concept for individually optimised treatment. (April 2021) - Van den Bosch, Lisa; van der Schaaf, Arjen; van der Laan, Hans Paul; Hoebers, Frank J.P.; Wijers, Oda B.; van den Hoek, Johanna G.M.; Moons, Karel G.M.; Reitsma, Johannes B.; Steenbakkers, Roel J.H.M.; Schuit, Ewoud; Langendijk, Johannes A.
Highlights: Comprehensive individual toxicity risk profile for head and neck cancer patients. Longitudinal risk prediction of 22 common radiation-induced toxicities. Fourteen organs at risk and integral radiation dose were associated with toxicity. Oral cavity was predominantly involved and therefore critical to spare. Stepping stone towards individualised optimisation of radiation treatment. Abstract: Background and purpose: A comprehensive individual toxicity risk profile is needed to improve radiation treatment optimisation, minimising toxicity burden, in head and neck cancer (HNC) patients. We aimed to develop and externally validate NTCP models for various toxicities at multiple time points. Materials and methods: Using logistic regression, we determined the relationship between normal tissue irradiation and the risk of 22 toxicities at ten time points during and after treatment in 750 HNC patients. The toxicities involved swallowing, salivary, mucosal, speech, pain and general complaints. Studied predictors included patient, tumour and treatment characteristics and dose parameters of 28 organs. The resulting NTCP models were externally validated in 395 HNC patients. Results: The NTCP models involved 14 organs that were associated with at least one toxicity. The oral cavity was the predominant organ, associated with 12 toxicities. Other important organs included the parotid and submandibular glands, buccal mucosa and swallowing muscles. In addition, baseline toxicity, treatment modality, and tumour site were common predictors of toxicity. The median discrimination performance (AUC) of the models was 0.71 (interquartile range: 0.68–0.75) at internal validation and 0.67 (interquartile range: 0.62–0.71) at external validation. Conclusion: We established a comprehensive individual toxicity risk profile that provides essential insight into how radiation exposure of various organs translates into multiple acute and late toxicities. This comprehensive understanding of radiation-induced toxicities enables a new radiation treatment optimisation concept that balances multiple toxicity risks simultaneously and minimises the overall toxicity burden for an individual HNC patient who needs to undergo radiation treatment.